Constructing Motivational Meaning through Self-Mention Markers in Joshua Hong’s UNESCO Speeches - Ratri Izzati Zharfa; Widhiyanto (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
Motivational speeches by public figures play a critical role in inspiring audiences, fostering engagement, and promoting social responsibility. This study investigates how self-mention markers contribute to the construction of motivational meaning in Joshua Hong’s UNESCO speeches. Guided by Hyland’s (2005) interactional metadiscourse framework, a qualitative discourse analysis was conducted on two speeches delivered at the UNESCO Youth Forum (2023) and the Goodwill Ambassador for Youth Nomination Ceremony (2024). A total of 93 self-mention markers were identified, with we, our, and us being the most frequent. Four main functions were found: constructing collective identity, expressing commitment and responsibility, sharing personal experiences and authenticity, and highlighting perseverance and struggle. The findings indicate that motivational meaning is discursively constructed through these markers, fostering solidarity, credibility, collective responsibility, and resilience among audiences. Self-mention markers thus function as central interpersonal resources in motivational discourse, highlighting the role of strategic speaker positioning in shaping audience engagement and motivation.